The Effect of Organic and Inorganic Modifiers on the Physical Properties of Granite Residual Soil - Bingxiang Yuan; Weijie Chen; Jin Zhao; Fei Yang; Qingzi Luo; Tianying Chen (Advances in Materials Science and Engineering)
As a kind of highly weathered special soil in South China, granite residual soils (GRS) feature high strength and high void ratio in a dry environment, so they tend to disintegrate in water and cause geological disasters including collapse. Therefore, modifying GRS for higher strength has become a hot spot. Glass fiber reinforced soils boast fewer cracks, higher energy absorption, and residual strength. This study aims to analyze the reinforcement effect of glass fibers on GRS with inorganic and organic solutions and its environmental feasibility. The inorganic solution contains silicon ion and sodium ion at the ratio of 1 : 4 (hereinafter referred to as Si : Na = 1 : 4 solutions), and the organic one is a modified polyvinyl alcohol solution (hereinafter referred to as SH solution). The reinforced samples were subjected to plate and impact load tests, SEM, and XRD analysis to investigate their mechanical properties, microcharacteristics, and the components produced. Results indicate that the reinforcement effect of glass fibers on GRS under Si : Na = 1 : 4 solutions was better than that of SH solutions. After being reinforced by Si : Na = 1 : 4 solutions, the samples reached maximum impact resistance. SEM results show that glass fibers bond more soil and form an integral structure; thereby the strength was improved as glass fibers share external impact load. XRD results show that geopolymer and alkali-activated materials and potassium feldspar were formed. Geopolymer and alkali-activated materials are pollution-free, inorganic polymers featuring viscosity and high compressive strength. Potassium feldspar is an aluminosilicate mineral with high strength and stable chemical properties, which can adhere to more granules and form a stronger whole structure with geopolymers playing a role. Therefore, it is feasible to reuse these soils sustainably by reinforcing them with glass fibers and the best Si : Na = 1 : 4 solutions. This study finds a new direction for recycling and reusing construction waste, GRS.